Memahami Pesan Dakwah Dalam Siaran - Effendy, Erwan; Panjaitan, Fatwa Perdana; Azmi, Fauzan (Da'watuna: Journal of Communication and Islamic Broadcasting, 2023)
Dakwah, which initially only used traditional media, has developed by incorporating elements of contemporary technology, such as radio and television. One of the modern media that can be used for preaching today is radio and television. The purpose of television is to attract people's attention to the content of the message. Television has the potential to be an attractive medium for communicating positive messages to society. contains religious messages commonly called da'wah. The superiority of da'wah conveyed through broadcast media is not the only factor that plays a role. In this study, content analysis was used. Likewise, a da'i who wants to utilize broadcast media must have a deep understanding of how to do so, including how to determine the methods and techniques of his da'wah. Because the use of inappropriate broadcast media will not only waste time and money, but will also complicate the distance between da'wah activities and the community. Keywords: Da'wah, Contents of Da'wah Messages, Da'wah Material.